PERAWATAN PAYUDARA TERHADAP BENDUNGAN ASI - Yuli Suryanti; Rispa Rizkia; Rina Utami (LPPM STIKes Mitra Adiguna, 2022)
One of the problems during the puerperium is swollen breasts or breast milk dams. The cause of breast milk dam is breast milk that is not immediately released, causing the breast to swell. This study aims to determine breast care for breast milk dams in postpartum mothers. This research method uses a qualitative approach to the type of phenomenology, namely by explaining the concept or phenomenon of experience in each individual. This research was conducted on postpartum mothers who experienced breast milk dams at BPM Sri Nirmala Palembang so that there were no limitations in interpreting or understanding the phenomena studied with the aim of obtaining in-depth information and providing greater understanding. The results of the study obtained by researchers regarding the dam of breastfeeding mothers after childbirth are: 1) breast engorgement due to late breastfeeding 2) breast milk dam 3) breast hygiene. Breast and nipple care is very important in the lactation process for mothers in going through the early days of breastfeeding which can sometimes feel very heavy. Conclusions from interviews and observations on Mrs. Y and Mrs. W is not as good at doing breasts as the midwife explained. Keywords: Breast Care, Breastfeeding Dam